Exploring the Black Box: An Analysis of Work Group Diversity, Conflict and Performance - Pelled, Lisa Hope; Eisenhardt, Kathleen M.; Xin, Katherine R. (Administrative Science Quarterly, 1999)
In this paper we present an integrative model of the relationships among diversity, conflict, and performance, and we test that model with a sample of 45 teams. Findings show that diversity shapes conflict and that conflict, in turn, shapes performance, but these linkages have subtleties. Functional background diversity drives task conflict, but multiple types of diversity drive emotional conflict. Race and tenure diversity are positively associated with emotional conflict, while age diversity is negatively associated with such conflict. Task routineness and group longevity moderate these relationships. Results further show that task conflict has more favorable effects on cognitive task performance than does emotional conflict. Overall, these patterns suggest a complex link between work group diversity and work group functioning.